Refractive errors during pregnancy: A bibliographic review - Cavalli , Ana Paula; Bettes , Paulo Sérgio Loiácono; Friedrich, Ana Paula; Hammes, Bruna; Boldori, Beatriz Peruzzolo; Sampaio, Erika; Bettes, Julia Buquera (Seven Editora, 2023)
Introduction: During pregnancy, many physiological changes occur in women secondary to the metabolic demands of the fetus, placenta, and uterus and the increasing levels of sex hormones. The hormonal peak is characterized by the increase in estrogen, progesterone, and androgen which have receptors in various tissues, with the ability to modify them. The purpose of the research is to analyze the emergence/progression of refractive errors during pregnancy, describe the pathophysiology, identify if there is an improvement in the postpartum period, if there is a need for treatment, and verify the relationship between the mode of delivery and the RE. Material and methods: A bibliographic review was carried out with research restrictions from 2000 to 2022, being selected thirty-one studies. It also had a theoretical basis in books and reports. Results and discussions: Since the gestational period is related to physiological, pathological changes or changes in certain conditions, we have to take into account that the ocular tissues can change. The presence of sex hormone receptors in eye tissues been observed, which are affected during pregnancy, causing eye disorders to be exacerbated or ameliorated. Conclusion: Most authors conclude that RE can occur during pregnancy, however, many have inconclusive results. RE are physiological changes during this period, not requiring treatment, as they tend to regress after delivery. Changes in the RE and the mode of delivery should not be taken into account. More research is needed on the subject, as many articles contradict each other, despite the changes in the cornea being confirmed. DOI:https://doi.org/ 10.56238/devopinterscie-140